Molecular Docking Studies of Wildtype P53 with Damnacanthal and Scopoletin- Phytochemicals Derived from Morinda Citrifolia - Radhika Nagre (International Journal of Molecular Biotechnological Research, 2023)
Cancer is a prominent cause of mortality globally, and it has the potential to impact any region of the body. The tumor suppressor protein P53 plays a significant role in inhibiting tumor growth by regulating DNA repair, inducing cell cycle arrest, promoting senescence, and triggering apoptosis when confronted with genotoxic stress. P53 is found mutated in 50% of cancers where it loses its tumor suppressive properties and gains oncogenic properties where it functions in a contradictory way in cancer cells when compared to normal cells. The mutated P53 forms oligomers with wtP53 rendering it incapable of carrying out its apoptotic functions and instead uses its prosurvival functions in promoting the tumor growth. Small ligand molecules that can bind the wtP53 and inhibit its oligomerisation with mutant P53 can be a possible therapy for cancer. Another possibility of targeting wtP53 in a cancer cell can be the induction of apoptotic function instead of pro-survival function which can be useful in eliminating the cancer cell whose damage is beyond repair. There are various therapeutic interventions available for cancer therapy but they are not without serious side effects which generates a need to develop drugs that do not have many side effects and that do not harm normal cells. In present times plant based phytochemicals have gained recognition for having many anticancer therapeutic properties among which Morinda citrifolia, also known as noni is found to have many phytochemicals with anticancer effects that can be exploited as potential therapy for cancer. In this study we used two PDBID structures of P53, PDBID-6FF9, containing the N-terminal domain (NTD) and the DNA binding domain (DBD) and PDBID-3SAK containing only the tetramerisation domain (TD) of wtP53 and analysed the docking of these structures with two of the phytochemicals (Damnacanthal, Scopoletin) present in Morinda citrifolia which are known to have potential anticancer therapeutic value. The two ligands were found to interact with the protein and the best docking position with the lowest binding energy was selected and reported in this paper
Keywords: Damnacanthal; Morinda citrifolia; Phytochemicals; Scopoletin; Tumor suppressor protein P53